Macrophage in asthma - Robinson, Douglas (Henry Stewart Talks, 2012)
Contributing factors to asthma include abnormal epithelium, predominant Th2 cytokines, and inappropriate repair leading to airway remodeling, Alternative activation of macrophages (via IL-4 and IL-13) leads to chitinase production, Interstitial macrophages may have regulatory role (via IL-10), IL-13 may be a key cytokine in activation of airway macrophages, IL-13 amplifies features of asthma such as airway hyperresponsiveness and mucus production